11β-Hydroxysteroid dehydrogenase 1 deficiency prevents PTSD-like memory in young adult mice. (December 2022) - Wheelan, Nicola; Seckl, Jonathan R.; Yau, Joyce L.W.
Abstract: Post-traumatic stress disorder (PTSD) is characterized by the co-existence of a persistent strong memory of the traumatic experience and amnesia for the peritraumatic context. Most animal models, however, fail to account for the contextual amnesia which is considered to play a critical role in the etiology of PTSD intrusive memories. It is also unclear how aging affects PTSD-like memory. Glucocorticoids alter the formation and retention of fear-associated memory. Here, we investigated whether a deficiency of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) (an intracellular glucocorticoid generating enzyme) and aging modulates fear conditioning and PTSD-like memory in mice. We first measured memory in 6 months and 24 months old 11β-HSD1 deficient (HSD1 KO) and wildtype (WT) mice following paired tone-shock fear conditioning. Then, separate groups of mice were exposed to restraint stress immediately after unpaired tone-shock contextual fear conditioning. Compared with young controls, aged WT mice exhibited enhanced auditory cued fear memory, but contextual fear memory was not different. Contextual fear memory retention was attenuated in both young and aged HSD1 KO mice. In contrast, auditory cued fear memory was reduced 24 h after training only in aged HSD1 KO mice. When fear conditioned with stress, WT mice displayed PTSD-like memory (i.e., increased fear to tone not predictive of shock and reduced fear to 'aversive' conditioning context); this was unchanged with aging. In contrast, young HSD1 KO mice fear conditioned with stress showed normal fear memory (i.e., increased fear response to conditioning context), as observed in WT mice fear conditioned alone. While aged HSD1 KO mice fear conditioned with stress also displayed normal contextual fear memory, the fear response to the 'safe' tone remained. Thus, a deficiency of 11β-HSD1 protects against both amnesia for the conditioning context and hypermnesia for a salient tone in young adult mice but only contextual amnesia is prevented in aged mice. These results suggest that brain 11β-HSD1 generated glucocorticoids make a significant contribution to fear conditioning and PTSD-like memory. 11β-HSD1 inhibition may be useful in prevention and/or treatment of PTSD. Highlights: 11β-HSD1 deficiency attenuates fear conditioning in 6 months and 24 months old male mice. Auditory cued fear memory is enhanced with aging. Restraint stress immediately after fear conditioning induces PTSD-like memory: both enhanced fear memory for a salient tone (not predictive of shock) and amnesia for the 'aversive' conditioning context. 11β-HSD1 deficiency prevents PTSD-like memory in young adult mice, but the abnormal fear response to the 'safe' tone persists in aged mice.